(untitled) (Journal of the Management Sciences, 2024)
As the world becomes more globally connected with dynamics in business and increase stakeholders’ knowledge-based on sustainability, accountability and transparency in reporting, corporations around the globe have found it imperative to shift from one-dimensional financial reporting towards the integration of non-financial reporting. Consequently, many researchers have studied the effect of social and environmental accounting and how it relates to corporate performance. However, these studies ignore consumable firms whose activities have resulted into health hazard to human life and detriment to the ecosystem. Therefore, this study examined the effect of social and environmental accounting on performance of listed consumable firms in Nigeria for the period 2011-2020. The twentyfive (25) listed consumable firms in the Nigeria Stock Exchange as at 31st December 2020 constituted the population out of which fifteen (15) were purposively drawn as sampled firms. Secondary quantitative data, sourced from the sampled firms’ financial reports and publications of Nigeria Stock Exchange were employed. The study adopted multiple regression model using combined data of all selected firms to analyse the data and findings revealed social and environmental accounting proxied by labour force costs and solid waste management costs respectively had significant positive effect on earnings per share, return on assets and return on equity respectively (corporate performance variables). The study therefore, recommended among others that consumable firms in Nigeria should make more effort to increase their commitment to social and environmental responsibility and also ensure proper accounting and disclosure of costs implication of such activities as this will increase their financial performance.